Regulation of protein kinase TAK1 - Liu, Xinyu (2010)
This study was focused on the exploration of new regulators of TAK1, a critical kinase lying near the top of multiple pro-inflammatory signaling cascades, by identifying novel interacting proteins of TAK1, which hopefully will facilitate development of potential therapeutics for chronic inflammatory diseases such as rheumatoid arthritis. Firstly, TAK1 was identified as Hsp90 client kinase using endogenous and exogenous systems. Hsp90 directly binds to kinase domain of TAK1, while the kinase activity of TAK1 as well as autophosphorylation of TAK1 at its activation loop was not required for the binding. TAB1/2/3, the binding partners of TAK1, did not interact with Hsp90, however, interaction of TAK1-Hsp90 was found to be significantly attenuated by TAB1 regardless of TAK1 activation states whereas TAK1-TAB1 binding was not affected by overexpression of Hsp90 in HEK293 cells. This result was supported by TAB1 knockdown experiment which led to increased binding of Hsp90 to TAK1. Hsp90 was not required for TAK1 activation since phosphorylation of TAK1 activation loop was unaffected when Hsp90-TAK1 interaction was disrupted by using Hsp90 inhibitor in a short term. Nonetheless, it was required for TAK1 stability because prolonged inhibition of Hsp90 resulted in down-regulation of endogenous TAK1 but not its binding partners (TAB1, TAB2 and TAB3).